2017
DOI: 10.1016/j.celrep.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Dihydroceramides Are Diabetes Susceptibility Biomarker Candidates in Mice and Humans

Abstract: Plasma metabolite concentrations reflect the activity of tissue metabolic pathways and their quantitative determination may be informative about pathogenic conditions. We searched for plasma lipid species whose concentrations correlate with various parameters of glucose homeostasis and susceptibility to type 2 diabetes (T2D). Shotgun lipidomic analysis of the plasma of mice from different genetic backgrounds, which develop a pre-diabetic state at different rates when metabolically stressed, led to the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
162
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 36 publications
17
162
0
1
Order By: Relevance
“…very recently reported that the urinary ceramide levels were higher in 15 children with type 1 diabetes than in 35 healthy children, the present study is the first study to show associations between urinary ceramides and the stages of diabetic nephropathy or clinical parameters for diabetic nephropathy in adults. As for the classes of ceramides, previous studies have reported that the plasma Cer C18:0, C20:0 C22:0, C24:1 and dihydro Cer C22:0 levels were higher in patients with diabetes, with similar changes in the urinary levels of ceramides observed in the present study. Hilvo et al.…”
Section: Discussionsupporting
confidence: 89%
“…very recently reported that the urinary ceramide levels were higher in 15 children with type 1 diabetes than in 35 healthy children, the present study is the first study to show associations between urinary ceramides and the stages of diabetic nephropathy or clinical parameters for diabetic nephropathy in adults. As for the classes of ceramides, previous studies have reported that the plasma Cer C18:0, C20:0 C22:0, C24:1 and dihydro Cer C22:0 levels were higher in patients with diabetes, with similar changes in the urinary levels of ceramides observed in the present study. Hilvo et al.…”
Section: Discussionsupporting
confidence: 89%
“…Ceramides can be detected in blood samples and have been proposed as a disease biomarker [85]. Wigger et al [90] in 2017 reported that plasma dihydroceramides are important predictors of diabetes and confirmed in two cohort studies that dihydroceramide levels are increased up to 9 years before the onset of diabetes in people at risk of developing the disease. In particular, higher plasma concentrations of ceramides C18:0, C20:0, C24:1 have been found in people with Type 2 diabetes compared to control subjects [52], and plasma C18:0, C20:0, C22:0 and some dihydroceramide species were significantly elevated in plasma of people with Type 2 diabetes many years prior to diabetes diagnosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role and mechanisms underlying the contribution of ceramides to the development of insulin resistance in various tissues [4,5]. Moreover, it was recently demonstrated in both mice and humans that concentrations of plasma dihydroceramides, ceramide precursor molecules, are already elevated years before the onset of type 2 diabetes [6]. We previously described the value of three ceramides [Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/24:1)] and their ratios to Cer(d18:1/24:0) in predicting cardiovascular risk, especially cardiovascular death, in both secondary and primary prevention cardiovascular studies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We previously described the value of three ceramides [Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/24:1)] and their ratios to Cer(d18:1/24:0) in predicting cardiovascular risk, especially cardiovascular death, in both secondary and primary prevention cardiovascular studies [7,8]. Prior results suggest that one of these ceramides, Cer(d18:1/18:0), was also able to predict the risk of future type 2 diabetes [6]. The aim of the present study was to investigate how these cardiovascular disease-associated ceramides predict incident type 2 diabetes and are modulated by lifestyle intervention.…”
Section: Introductionmentioning
confidence: 99%